Harrison's neurology in clinical medicine - Harrison, Tinsley Randolph 1900-1978; Hauser, Stephen L.; Josephson, Scott Andrew (McGraw-Hill Medical, 2013)
Featuring a superb compilation of chapters related to neurology that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Features: Current, complete coverage of clinically important topics in neurology, including Clinical Manifestations of Neurologic Diseases, Diseases of the Nervous System, Chronic Fatigue Syndrome, Psychiatric Disorders, and Alcoholism and Drug Dependency. NEW CHAPTERS discuss the pathogenesis and treatment and syncope; dizziness and vertigo; peripheral neuropathy; neuropsychiatric problems among war veterans; and advances in deciphering the pathogenesis of common psychiatric disorders. Integration of pathophysiology with clinical management. 118 high-yield questions and answers drawn from Harrison's Principles of Internal Medicine Self-Assessment and Board Review, 18 edition. Content updates and new developments since the publication of Harrison's Principles of Internal Medicine, 18 edition, 58 chapters written by physicians who are recognized experts in the field of clinical neurology. Helpful appendix of laboratory values of clinical importance.